Census of Tribal Justice Agencies, 2002 ([Verlag nicht ermittelbar], 2006)
The study compiles data on the law enforcement, courts and administration, corrections and intermediate sanctions, criminal history records, and justice statistics of the federally recognized American Indian tribal governing bodies. The data determine which tribes have sworn law enforcement personnel and the source of authority, what the number and type of tribal court systems are, who performs the tribal detention function and what types of sanctions are imposed. It also looks at whether tribes have access to state and national criminal record systems.